Do Thor and Odin Have Bodies? Superperception and Divine Intervention among the Old Norse Gods - Taggart, Declan (Religions, 2019)
In Old Norse mythology, gods like Freyja, Odin, and Thor are usually characterized as human-like creatures: they walk and ride animals, eat, grow old, and even die. Was there more to conceptions of Old Norse gods than those anthropomorphic representations? This article presents evidence that the gods of early Scandinavia were sometimes thought of as superperceiving and able to act in ways that defied the limitations of a physical body. It engages with and challenges theological correctness, a prominent theory in the Cognitive Science of Religion, to elucidate the sources of Old Norse religion and the cognitive and contextual foundations of the representations of gods encountered there. Following an examination of the mechanisms through which Old Norse gods' superperception and disembodied action were narrativized and rationalized, the article concludes with a discussion of the consequences of non-anthropomorphic representations of the gods for understanding Scandinavian worshippers' everyday religious life.